Asuhan Keperawatan Pada Ny. N Dengan Medis Diabetes Melitus (DM) Di RSD Gunung Jati - Fitriyani, Risma; Purbasari, Dwiyanti; Komariyah , Oom; Sari, Diana; Dwi Hikmatun , Khaerunnisa (MEJORA Medical Journal Awatara, 2024)
Diabetes Mellitus is a disease in the form of increased blood glucose levels or commonly called hyperglycemia that exceeds normal limits. This condition is caused by a decrease in insulin secretion that occurs due to dysfunction in the pancreas, insulin sensitivity is decreasing, or from both, Diabetes Mellitus (DM) is a disease whose number of sufferers continues to increase cases every year. This study uses a case study method with female patient respondents aged 38 years with a medical diagnosis of diabetes mellitus. Data collection techniques are carried out by interviews (interview results contain the identity of the client, main complaints, history of current and past diseases), observation and physical examination. This research was carried out in the HCU Room of Gunung Jati Hospital, Cirebon City for 3 days (March 11, 2024 – March 13, 2024). the results of a case study in patients with diabetes mellitus obtained a nursing diagnosis there was a wound in the left leg area, during nursing care for 3 days it was found that the problem was resolved so that the intervention was stopped. based on the results of the evaluation of the wound problem in the left leg area in the patient can be resolved.